Efektifitas Terapi Musik Dangdut dalam Menurunkan Halusinasi pada Pasien Skizofrenia: Studi Kasus - Luthfiana Sukma Rantikasari; Milkhatun Milkhatun; Dwi Rahmah Fitriani; Arief Budiman (Poltekkes Kemenkes Padang, 2026)
Hallucinations in patients with schizophrenia can disrupt psychosocial functioning and increase the risk of maladaptive behaviors, highlighting the need for effective and contextually appropriate non-pharmacological interventions. This study aimed to evaluate the implementation of dangdut music therapy in reducing the level of hallucinations among patients with schizophrenia. A case study design was employed using a psychiatric nursing care approach involving one patient at Atma Husada Mahakam Psychiatric Hospital, Samarinda. The intervention consisted of dangdut music therapy administered for approximately 15–30 minutes per session, once daily for five consecutive days. Hallucination levels were measured using the Auditory Hallucinations Rating Scale (AHRS) before and after the intervention. The results demonstrated a reduction in the AHRS score from 28 (moderate–severe category) to 14 (mild–moderate category), accompanied by a decrease in hallucination frequency from 5–6 episodes per day to 1–2 episodes per day and a reduction in emotional response intensity from a score of 4 to 2. These findings suggest that dangdut music therapy has the potential to help reduce hallucination severity in patients with schizophrenia. In conclusion, dangdut music therapy may serve as a beneficial complementary intervention for managing hallucinations in schizophrenia within the context of a case study. However, further studies with larger sample sizes and more rigorous research designs are needed to confirm its effectiveness on a broader scale.